2015
DOI: 10.1177/1470320315575849
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular actions of mineralocorticoid receptor antagonists in patients with chronic kidney disease: A systematic review and meta-analysis of randomized trials

Abstract: Introduction: The safety and actions of mineralocorticoid receptor antagonists on surrogate markers of cardiovascular disease as well as major patient level cardiovascular end-points in patients with chronic kidney disease are unclear. Methods: MEDLINE, EMBASE, Trip Database, Cochrane Central Register of Controlled Trials, Cochrane Renal Group specialized register, Current Controlled Trials and clinicaltrials.gov were searched for relevant trials. Results: Twenty-nine trials (1581 patients) were included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 47 publications
3
14
0
Order By: Relevance
“…These findings are in keeping with previous published meta-analyses [15, 16, 20]. By using additional unpublished summary results from a number of authors, we ensure that our protein/albumin excretion data are more comprehensive and hence more accurate.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…These findings are in keeping with previous published meta-analyses [15, 16, 20]. By using additional unpublished summary results from a number of authors, we ensure that our protein/albumin excretion data are more comprehensive and hence more accurate.…”
Section: Discussionsupporting
confidence: 75%
“…The beneficial effects on outcomes were confounded by increased risk of hyperkalaemia, a factor limiting MRA prescribing in CKD [1719]. Similar findings were described in a more recent meta-analysis on the cardiovascular actions of MRAs in CKD [20]. However, the conclusions of these analyses are drawn from mainly published proteinuria data only, derived by consolidating disparate urinary protein excretion measures used in different trials (variably reported as protein or albumin excretion in spot samples or 24 h collections).…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Interestingly, Ng et al found in their meta-analysis of 28 studies that the use of MR antagonists was associated with increased serum potassium and a higher risk ratio of hyperkalemia. 35 A possible explanation is that Ng included patients with chronic kidney disease (CKD) of stage I to stage V, while this review only included patients receiving hemodialysis.…”
Section: Discussionmentioning
confidence: 99%